PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS SOSIAL HUMANISTIK DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK SEKOLAH DASAR - Rosidah Aliim Hidayat; Zainnur Wijayanto (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this research and development research was (1) to produce a humanistic social-based learning model that was suitable for the mathematical communication skills of elementary school students and (2) to test its effectiveness. The type of research used was RnD with a 4-D development model developed by Thiagarajan. The research subjects on a small scale were 4 students of grade IV and on a wide scale were all students in grade IV of SD Taman Muda IP. The data analysis technique used descriptive qualitative and quantitative. Qualitative analysis technique was used to describe the stages of developing a humanistic social-based learning model in improving mathematical communication skills. Quantitative analysis techniques were utilized to test the validity, practicality, and effectiveness. Based on research data, validation tests from experts and practitioners, it can be concluded that the humanistic social-based learning model in improving the mathematical communication skills of elementary school students was valid, practical, and effective. After going through the validation stage, both experts and practitioners, the product developed was said to be valid (feasible and can be used). After being tested on a small scale and a large scale, the product developed was included in the practical and effective criteria. Thus, the developed model can be used as reference material in enriching the learning process in elementary schools so that it is hoped that student learning outcomes can alsobe enhanced Keywords: humanistic, communication, mathematics, social. References: Aloni, N. 2013. Empowering dialogues in humanistic education. Educational Philosophy and Theory, 45(10), 1067-1081. Ansari, B. I. 2012. Komunikasi Matematik dan Politik. Banda Aceh: Yayasan Pena. Annisa, W.N. 2014. “Peningkatan Kemampuan Pemecahan Masalah Dan Komunikasi Matematik Melalui Pembelajaran Pendidikan Matematika Realistik Untuk Siswa SMP Negeri Di Kabupaten Garut”. Jurnal Pendidikan dan Keguruan Vol. 1 No. 1, artikel 8. Ärlebäck, J.B., & Doerr, H.M. 2017. Students’ interpretations and reasoning about phenomena with negative rates of change throughout a model development sequence. ZDM - Mathematics Education, 50(1–2), 187–200. Bozkurt, G. 2017. Social Constructivism: Does It Succeed in Reconciling Individual Cognition with Social Teaching and Learning Practices in Mathematics?, Journal of Education and Practice, 2017. Journal of Education and Practice, 8(3), 210–218. Cole, M. 1985. The Zone of Proximal Development: Where Culture and Cognition Create Each Other. In J.V. Wertsch (ed.), Culture, Communication and Cognition, p. 146-161. Cambridge: Cambridge Darminto, B. 2014. Penerapan Teori Maslow Pada Pembelajaran Matematika di SD. Jurnal Pendidikan, Volume 23, Nomor 1. Deaton, S. 2015. Social learning theory in the age of social media: Implications for educational practitioners. Journal of Educational Technology, 12(1), 1-6. Friedlaender, D. 2019. A Humanistic Approach to Scaling Up. Research Brief. Stanford Center for Opportunity Policy in Education. Gmaj, I., & Fijałkowska, B. 2021. Between a humanistic and economic model of lifelong learning: The validation system in Poland. European Journal of Education, 56(3), 407-422. Herring, C., Rosaldo, M., Seim, J., & Shestakofsky, B. 2016. Living theory: Principles and practices for teaching social theory ethnographically. Teaching Sociology, 44(3), 188-199. Jorgensen, R., Gates, P., & Roper, V. 2014. Structural exclusion through school mathematics: Using Bourdieu to understand mathematics as a social practice. Educational Studies in Mathematics, 87(2), 221-239. Kemdikbud. 2013. Modul Pelatihan Implementasi Kurikulum 2013. Jakarta: Badan Pengembangan Sumberdaya Manusia Pendidikan dan Kebudayaan. Kirschner, P.A., Sweller, J., & Clark, R.E. 2006. Why Minimal Guidance During Instruction Does Not Work: An Analysis of the Failure of Constructivist, Discovery, Problem-Based, Experiential, and Inquiry-Based Teaching. Educational Psychologist, 41(2), 111–127. Koswara, D. 2015. Pembelajaran Kreatif dan Bermakna. Bandung: Universitas Pendidikan Indonesia Lerman, S. 2000. The social turn in mathematics education research. Multiple perspectives on mathematics teaching and learning, 1, 19-44. Lestari, L.A.S., Sumantri, & Suartama. 2014. Pengaruh Model Pembelajaran Bandura Terhadap Kinerja Ilmiah dan Hasil Belajar IPA Peserta didik Kelas IV SD. Jurnal Mimbar PGSD Universitas Pendidikan Ganesha Jurusan PGSD., Vol: 2 No: 1. Lipeikienė, J. 2009. Development of a Mathematical Communication Curriculum. Informacijos Mokslai/Information Sciences, 50. Morris, C.W. 1994. Norm, Values, and Society. Wien: Kluwer Academic Publisher. Moshman, D. 1998. Cognitive development beyond childhood. In W. Damon (Series Ed.) Mullis, I.V., Martin, M.O., Foy, P., & Arora, A. 2012. TIMSS 2011 international results in mathematics. International Association for the Evaluation of Educational Achievement. Herengracht 487, Amsterdam, 1017 BT, The Netherlands. NCTM. 2000. Principles and standards for school mathematics. Reston, VA: NCTM. Pais, A., & Valero, P. 2014. Whither social theory?. Educational Studies in Mathematics, 87(2), 241-248. Palincsar, A.S. 1998. Keeping the metaphor of Sfresh – A response to C. Prawat, R.S. 1992. Teachers’ Beliefs about Teaching and Learning: A Constructivist Perspective. American Journal of Education, 100(3), 354–395. Puskur. 2002. Kurikulum dan Hasil Belajar. Kompetensi Dasar Mata Pelajaran Matematika Sekolah Dasar dan Madrasah Ibtidaiyah. Jakarta: Balitbang Depdiknas. Ramdani, Y. 2012. “Pengembangan Instrumendan Bahan Ajar untuk Meningkatkan Kemampuan Komunikasi, Penalaran, dan Koneksi Matematisdalam Konsep Integral”. Jurnal Penelitian Pendidikan. Vol. 13. No. 1, pp. 47-48. Rismawati, M., & Setiawan, B. 2017. Membangun Kemampuan Komunikasi Matematis Peserta Didik pada Mata Kuliah Konsep Dasar Matematika SD Prodi PGSD. Jurnal Pendidikan Dasar PerKhasa, 3(2), 462–472. Sapriati, A., & Zuhairi, A. 2010. Using Computer-Based Testing as Alternative Assessment Method of Student Learning in Distance Education. Turkish Online Journal of Distance Education, 11(2), 161-169. Schneider, T.L. 2021. A social constructivist grounded theory of school principal legal learning. Journal of Research on Leadership Education, 16(3), 226-242. Sholeh, M. 2007. “Perencanaan Pembelajaran Mata Pelajaran Geografi Tingkat SMA dalam Konteks KTSP”. Jurnal Geografis FIS UNNES. Vol. 4, No.2, 129- 137. Suhendra. 2015. Pengembangan Kurikulum dan Pembelajaran Matematika. Jakarta: Universitas Terbuka Thiagarajan, S., Semmel, D.S. & Semmel, M.I. 1974. Instructional development for training teachers of exceptional children. Bloomington: Indiana University. Turmudi. 2009. “Students’S Responses To The Realistic Mathematics Teaching Approach In Junior Secondary School”, Indonesia University Of Education, Proceeding Of IICMA Van de Walle, J.A., Karp, K.S., & Bay-Williams, J. M. 2010. Elemnatary School Mathematics: Teaching developmentally (7th ed). Boston: Allyn & Balcon. Villares, E., Lemberger, M., Brigman, G., & Webb, L. 2011. Student Success Skills: An evidence‐based school counseling program grounded in humanistic theory. The Journal of Humanistic Counseling, 50(1), 42-55. Vygotsky, L.S. 1978. Mind In Society. Cambridge: Harvard University Press. Windshitl, M. 2004. The Challenges of Sustaining a Constructivist Classroom Culture, dalam Leonard Abbeduto, Taking Sides: Clashing Views on Controversial Issues in Educational Psychology, McGrawHill/Dushkin Woolfolk, A. 2009. Educational Psychology (8th ed.). New York: Allyn and Acon.